A Semantic Model Framework for the Cyber‐Physical Production System in the Systems Engineering Perspective. Issue 4 (12th January 2022) - SA, Puviyarasu; da Cunha, Catherine
ABSTRACT: A cyber‐physical production system (CPPS) is a system of digital and physical components with networked connections. These components are deeply intertwined and operate in situation‐dependent ways across all production levels. The system behavior is complex due to its dependencies and the relationship between its parts and their environment. The diversified components and their relationship lead to challenges for the involved actors in system development, operation, and end of life phases. There is a need for a generic semantic model framework to provide a unified description of all aspects and properties of the CPPS. In this paper, an overview and expected outcome of semantic model framework is presented. As a first step, the core elements, and boundaries of the CPPS are proposed. Based on a fundamental concept of systems engineering, the core elements are defined as a System of Interest (SOI) and Enabling Systems (ES).